Menggagas Fiqh Perempuan: Membangun Kekuatan Hukum Bagi Perempuan (Telaah Kritis Atas Pemikiran Kh. Husein Muhammad) - Abd. Warits (Proceedings of Annual Conference for Muslim Scholars, 2017)
The study on the relationship between women and men will never fade. This issue is always interesting as the various development issues era. Studie of Gender basically don't attempt to give birth to the women "revolt" over "power" male, but attempt to build "self-reliance" of women, as well as sensitize men that women have the status, rights and obligations are the same as man. This article examines the KH. Husein Muhammad thought’s about women's empowerment movement. On the basis of books and articles he wrote, the authors attempt to formulate his thoughts on the issue of women's empowerment. Additionally, the authors also examined other book with the theme of women which is then used as a comparison and analysis of materials in the formulation characteristics K. Husein’s thought. This study found that K. Hussein started the women's empowerment by: First, prove that Islam upholds the equality of all classes. Second, create a new interpretation to the verses of the Koran that seem "discriminatory" for women. Third, formulate jurisprudence (equality) of Women. jurisprudence is the "main gate" process of women empowerment because it is like the journey of life which guides contain technical rules and "impressed" is more sacred. Fourth, establish organizations that focus femaleness or study the problem of of womanhood and Fifth, Guarding of legislation of Indonesian law, to make it more "friendly" and provide the interests of women.Keywords: Women's Empowerment, Fiqh of Woment, And KH. Husein Muhammad